2018
DOI: 10.1155/2018/1659394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and Mexican Oregano (Lippia berlandieri Schauer) Essential Oil Added to Carboxymethyl Cellulose and Starch Edible Films on Listeria monocytogenes and Staphylococcus aureus

Abstract: e aim of this work was to evaluate the e ect of pH and Mexican oregano essential oil (MOEO) added to carboxymethyl cellulose (CMC) and starch (S) edible lms on Listeria monocytogenes and Staphylococcus aureus. CMC and S edible lms were formulated with di erent concentrations (0%, 0.25%, 0.50%, 0.75%, and 1%) of MOEO at di erent pH (5, 6, or 7). Antimicrobial assay was performed. Inhibition curves were tted to the Fermi model. Signi cant di erences (p < 0.05) were found in t c (time to reduce 50% of microbial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…On the other hand, N max is much closer to N 0 with a higher concentration of EO, indicating that there is a much greater bacterial effect, since it is possible to eliminate all the initial inoculum. Navarro-Cruz et al (2018) found that, when modeling the antibacterial effect of the essential oil of Lippia berlandieri against S. aureus , the time needed to decrease the initial inoculum by 50% was shorter when modifying the pH from 7 to 5 [ 36 ], coinciding with our findings for M. armillaris .…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, N max is much closer to N 0 with a higher concentration of EO, indicating that there is a much greater bacterial effect, since it is possible to eliminate all the initial inoculum. Navarro-Cruz et al (2018) found that, when modeling the antibacterial effect of the essential oil of Lippia berlandieri against S. aureus , the time needed to decrease the initial inoculum by 50% was shorter when modifying the pH from 7 to 5 [ 36 ], coinciding with our findings for M. armillaris .…”
Section: Discussionsupporting
confidence: 87%
“…OEO was more effective at pH 5.0; lower pH values increased the lag phase and reduced maximum growth. An acidic pH increases the OEO hydrophobicity, also increasing the dissolution of the membrane lipids, with the consequent interference with cellular functionality (Albuquerque et al, 2006;Rivera-Calo et al, 2015;Navarro-Cruz et al, 2018). The effect of pH is also related to the type of acid used to adjust the media, since organic acids are also mild antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…Another strategy is the preparation of packing materials, such as the edible coats and films formed with chitosan, carboxymethylcellulose, or starch and added with essential oils. Both strategies aim to distribute essential oils evenly and reduce interaction with food ingredients (Paparella et al, 2016;Basak and Guha, 2017;Navarro-Cruz et al, 2018;Ochoa-Velasco et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of them have been studied for their potential as food antimicrobials (Rivera-Calo et al, 2015;Swamy et al, 2016;Ambrosio et al, 2017;Rakmai et al, 2018). The use of natural compounds as food additives involves isolation, purification, stabilization, and incorporation of these compounds into food for antimicrobial purposes while maintaining the food's organoleptic and nutritive properties (Pandey et al, 2017;Rakmai et al, 2017a;Navarro-Cruz et al, 2018). The antimicrobial activity of these natural additives is due to the presence of their chemical compounds which can alter and penetrate the microorganism's cell wall lipid structure, disturbing cellular structures and leading to protein denaturation and cell membrane destruction, increasing their permeability and the likelihood of cytoplasmic ruptures, leaks, or cell lysis and eventually microbial death (Rakmai et al, 2017b;Reyes-Jurado et al, 2019).…”
Section: Introductionmentioning
confidence: 99%